Geographical Contexts of Entrepreneurship: Spaces, Places and Entrepreneurial Agency - Stam, Erik; Welter, Friederike (Taylor & Francis, 2020)
This chapter focuses on contexts of entrepreneurship, in particular geographical contexts, and entrepreneurial agency. The twin concepts space and place are key in understanding geographical contexts for entrepreneurship, not least because place does not exist without physical space. Important research in this regard has touched upon the role of gendered places and spaces for entrepreneurship, social places such as families, households and neighbourhoods and explored new spaces for entrepreneurship such as makerspaces. We combine these spaces and places in a model of entrepreneurial ecosystems that allows us to focus simultaneously on the geographical contexts for entrepreneurship and the agency of entrepreneurs within those. The chapter ends with a future research agenda on geographical contexts for entrepreneurship.
Keywords: Taverne; General Psychology; Economics, Econometrics and Finance(all); General Business,Management and Accounting